Evaluasi Kualitas Tanah Berbasis Sistem Infromasi Geografis di Lahan Sawah Kecamatan Denpasar Timur untuk Menentukan Arahan Pengelolaan - DARRYL CHRISTOPHER WENAS; A.A. NYOMAN SUPADMA; I DEWA MADE ARTHAGAMA (Agrotrop : Journal on Agriculture Science, 2023)
Evaluation of Soil Quality Based on Geographical Information Systems in Paddy Fields of East Denpasar District to Determine Land Management Directions. This study aims to determine soil quality, limiting factors, mapping of soil quality, and provide management directions or recommendations. This research was conducted in the rice fields of East Denpasar District from November 2020 to January 2021. This research was conducted using survey methods, soil analysis in the laboratory, and determination of soil quality. Soil samples were taken by purposive sampling technique on each homogeneous land unit. The homogenous land units determination is done by overlaying the soil types, slope maps and land use of the East Denpasar Subdistrict. Soil quality indicators measured as minimum data sets (MDS): soil bulk density, soil texture, porosity, field capacity water content, pH, C-organic, CEC, base saturation, nutrients (N, P and K), and C-biomass. The results of soil quality determination at each homogenous land units are mapped with QGIS 3.8.3 software and then the land management direction is determined for each homogenous land units. The results showed that the soil quality at the research site was classified as good at SLH 1 (Subak Padanggalak, Biaung, Poh Manis, Temaga, Taman, Dlod Sema and Buaji) and 3 (Subak Buaji, Padanggalak, Temaga, Taman, Anggabaya, Uma Desa and Uma Layu) with SQR values of 24 and 23. SLH 2 (Subak Biaung and Buaji), 4 (Subak Padanggalak), 5 (Subak Taman, Padanggalak and Paang) and 6 (Subak Paang and Saba) showed moderate soil quality with SQR scores were 26, 26, 27 and 27, respectively. The limiting factors in the study area include: N, P, texture, field capacity water content and C-biomass. It is recommended to cultivate the soil using a tractor and fertilize it with manure, urea and SP-36 in paddy fields.